2017
DOI: 10.14429/dlsj.2.12273
|View full text |Cite
|
Sign up to set email alerts
|

Application of Enriched Fraction of Seabuckthorn Leaf Extract as Antimicrobial Finish on Technical Textile

Abstract: Flavonoid-rich fraction (FRF) from Seabuckthorn leaves extract was prepared by acid hydrolysis process. Total flavonoid content of Seabuckthorn leaves extract and FRF estimated as rutin equivalent was found to be 116.98±3.06 and 277.14 ± 6.78 mg/g of extract/FRF respectively. Its major constituents myrcetin, quercetin, kaempferol and isorhamnetin, were determined by reverse phase high performance liquid chromatography (RP-HPLC). Aramid (NomexIIIA) fabric was treated with triethylene tetramine to increase the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The active constituents present in the plant used as plant defense mechanisms against the predation of different pathogenic microorganisms, insects, and herbivores. Soodinvestigated the application of herbal extracts on the fabric used for sanitary napkins by a pad-drycure method for antibacterial nature [18]. The results revealed that the methanolic extract of Bauhinia veriagata was showed an inhibition effect on S. aureus and Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…The active constituents present in the plant used as plant defense mechanisms against the predation of different pathogenic microorganisms, insects, and herbivores. Soodinvestigated the application of herbal extracts on the fabric used for sanitary napkins by a pad-drycure method for antibacterial nature [18]. The results revealed that the methanolic extract of Bauhinia veriagata was showed an inhibition effect on S. aureus and Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%